A Discourse on Abandoned Housing Projects (AHPs) and the Potential of Crowdfunding: Malaysian Evidence - Mohd Thas Thaker, Hassanudin (Global Review of Islamic Economics and Business, 2025)
The surge in housing demand has exacerbated challenges in Malaysia's property market, notably the widespread issue of abandoned housing projects (AHPs). Despite the government and banking sector's continuous efforts to facilitate financing for affordable housing, the increasing number of AHPs indicates economic inefficiencies. Literature identifies developers' financing constraints as a key driver of project abandonment. To address this, our study proposes the "Integrated Abandoned Housing Project Crowdfunding Model (IAHPCM)" as a viable alternative financing solution for developers. This framework aims to mitigate financial barriers and enhance housing project completion rates. The findings contribute to the growing body of literature on crowdfunding while offering practical implications for developers and broader economic sustainability.